Functional Income Distribution and Its Role in Explaining Inequality - Francese, Maura; Mulas-Granados, Carlos (Washington, D.C. : International Monetary Fund, 2015)
This paper is motivated by two parallel trends: the declining labor share of income and increasing inequality. Micro and macroeconomic data, covering up to 93 countries between 1970 and 2013, are used to assess whether the declining labor share of income has been a key factor driving growing inequality. The major conclusion is that changes in income inequality across a wide range of countries have been driven significantly by changes in the inequality of wages, while the distribution of income between labor and capital has not been a major factor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet